Plant-Based Therapies for Psoriasis Management - Rabia Anum*; Muhammad Akram; Imtiaz Mahmood Tahir*; Muhammad Wajid; Shamaila Kausar; Muhammad Bilal Afzal; Aniq Ur Rehman; Iftikhar Younis Mallhi; Shafqat Rasool; Fethi Ahmet Ozdemir; et al. (Dialogue Social Science Review (DSSR), 2025)
This study assesses the therapeutic efficacy of herbal interventions in the psoriasis management. The research investigates the pharmacological properties of phytochemical compounds, their mechanisms of action, and clinical benefits, to provide patients with evidence-based complementary therapeutic options while minimizing adverse effects. Deregulated T-lymphocyte-mediated immune responses cause erythematous, scaly plaques, which are the hallmark of psoriasis, a chronic inflammatory dermatosis. The condition encompasses two primary classifications: pustular psoriasis, including generalized pustular and palmoplantar variants, and plaque psoriasis, with psoriasis vulgaris representing the most prevalent subtype and carrying potential for systemic complications. The etiology remains incompletely understood, though immunological dysfunction and genetic predisposition are established as key pathogenic factors. Aberrant autoimmune responses are the principal drivers of accelerated keratinocyte proliferation in psoriasis, a process largely mediated by activated T-cells and the release of pro-inflammatory cytokines. Genetic susceptibility is evidenced through associations with specific HLA allotypes and polymorphisms at the PSORS1 locus. Environmental triggers, including streptococcal infections, viral illnesses, and physical trauma (Koebner phenomenon), may precipitate disease onset in genetically predisposed individuals. Psychological stress represents an additional contributory factor that can exacerbate disease activity through disruption of neuroendocrine, autonomic, and immune pathways. The findings demonstrate that herbal therapeutics constitute a safe and efficacious treatment modality for psoriasis. Bioactive botanical compounds exhibit anti-inflammatory and antipruritic properties whilst modulating immune system homeostasis. This therapeutic approach results in reduced treatment-related morbidity and enhanced patient outcomes.